Three new species of Ocotea (Lauraceae) from Brazilian Atlantic forest - Assis,Leandro C. S. (2009)
ABSTRACT Three new species of Ocotea - O. calliscypha L. C. S. Assis & Mello-Silva, from the state of Minas Gerais, O. ciliata L. C. S. Assis & Mello-Silva, from the state of Espírito Santo, and O. marcescens L. C. S. Assis & Mello-Silva, from the states of Bahia, Espírito Santo and Rio de Janeiro - are described. The species are illustrated, and comments on their relationships to other species of Ocotea, distribution, habitat, and phenology are provided.